2022
DOI: 10.37304/jcp.v10i2.7503
|View full text |Cite
|
Sign up to set email alerts
|

Development of Quick Response Code Based Learning Module on Human Reproductive System Materials to Increase Student Learning Outcomes.

Abstract: The objective of this research is to create a Quick Response Code equipped learning module on the human reproductive system that is applicable, doable, and efficient in enhancing student learning results. Students class XI from SMAN 3 Dusun Selatan served as the research subjects. research method Learning modules are created utilizing the ASSURE paradigm, which includes the following steps: (1) Analyze the Learner; (2) State Standards and Objectives; (3) Choose Methods; Media or Materials; (4) Utilize Media an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of QR codes varies based on subject area and grade level, offering a tailored approach to learning needs (Balintag & Wilang, 2020). Numerous studies explore QR codes in language teaching, detailing stages like code creation, mobile websites development, URL shortening, and automated code generation (Bella et al, 2022) QR codes find applications in educational settings, such as treasure hunts, outdoor activities, paper-based tasks, learner-generated content, and instructional guidance (Aziza, 2020;Andrzej et al,2021). For instance, in a treasure hunt, students demonstrate teamwork and problem-solving skills, fostering collaboration or competition.…”
Section: Literature Review Quick Response Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of QR codes varies based on subject area and grade level, offering a tailored approach to learning needs (Balintag & Wilang, 2020). Numerous studies explore QR codes in language teaching, detailing stages like code creation, mobile websites development, URL shortening, and automated code generation (Bella et al, 2022) QR codes find applications in educational settings, such as treasure hunts, outdoor activities, paper-based tasks, learner-generated content, and instructional guidance (Aziza, 2020;Andrzej et al,2021). For instance, in a treasure hunt, students demonstrate teamwork and problem-solving skills, fostering collaboration or competition.…”
Section: Literature Review Quick Response Codesmentioning
confidence: 99%
“…For instance, a study by Bahtiar & Sujono (2020) demonstrated that integrating QR codes into instructional materials significantly enhanced students' engagement and interaction with learning content. Similarly, (Bella et al, 2022) explored the integration of QR codes in classroom assessments and found that it streamlined the feedback process, fostering quicker and more effective communication between teachers and students. Additionally, the work of (Aziza, 2020) highlighted the role of QR codes in promoting collaborative learning experiences, enabling students to seamlessly share resources and collaborate on projects.…”
Section: Introductionmentioning
confidence: 99%